Penerapan E-Learning Mata Kuliah Matematika Ekonomi bagi Mahasiswa Ekonomi dan Bisnis Islam - Andang Sunarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Economics mathematics courses are abstract and require high thinking activities. Nevertheless, all students studying in the Islamic Economics study program FEBI IAIN Bengkulu must learn it because it is one of the compulsory subjects in the Islamic Economics program FEBI IAIN Bengkulu that must be taken. Learning mathematics economics needs to need learning media that can improve students' understanding in learning economic mathematics. With the media, students are given the ease of visualization of the material presented, including series, linear functions and things needed in economic mathematics learning. accurate for users so that they can be used as a choice of learning media in teaching and learning processes, inspire lecturers to use web media in the teaching and learning process and students can study anywhere without being limited by space and time. The method used is research and development or in English Research and Development is a research method that is used to produce certain products, and test the effectiveness of these products used in this study is the software used in this application is moodle, xampp and internet. Keywords :Moodle, Xampp, Internet.